Combined adjustment of angle and distance measurements in a dam monitoring network. Issue 342 (May 2015) - Casaca, J.; Braz, N.; Conde, V.
<x content-type="archive" xml:space="preserve">Abstract</x> The safety control and structural analysis of Portuguese large dams has been using, for many decades, small triangulation networks to monitor the horizontal displacements of a carefully selected set of target points on the dams. The recent surge in the use of motorised tacheometers, which enable automatic measurement of angles and distances, is changing traditional triangulation networks into combined angles/distances networks. This paper addresses the estimation of weights for the combined adjustment of angles and distances.